LEADING ACTIVITY ALLIVIATING THE PUPILS' HELPLESSNESS IN LEARNING PROCESS - B. A. Vjatkin; E. S. Davydova; E. V. Zabelina (Russian State Vocational Pedagogical University, 2015)
The research objective is to substantiate the possibility of overcoming the pupils' personal helplessness in educational process by stimulating the leading age-related activity. The methodology is based on the poly-system interaction. The applied methods include using various questionnaires for diagnosing the learning and communicative activities of primary and secondary school pupils. The experimental data analysis demonstrates that learning activity of primary school pupils and communicative activity of teenagers can be regarded as the ways for overcoming their personal helplessness in educational process. The research novelty implies the investigation of functional correlations between the respondents' personal helplessness and activity. The research outcomes provide the additional options for facilitating the self-sufficiency of primary and secondary school pupils, and mitigating their helplessness in educational process.